Rethinking Approaches to the Level System of Higher Education in Russia in the Context of the Country’s Withdrawal from the Bologna Process - L. V. Konstantinova; A. M. Petrov; D. A. Shtykhno (Высшее образование в России)
Withdrawal from the Bologna Process has initiated discussions of future development of the level system of higher education in the Russian Federation. The article systematizes the main directions of criticism of the “Bolognaization” of Russian higher education and presents the author’s approach to rethinking the level system, formulating proposals for its new outlook. It is indicated that in view of the dynamic nature of the professional sphere and the growth of professional mobility, the multi-level system of higher education tends to be more promising, and it is advisable to build its new contours ensuring its multi-format, structural flexibility, openness, internal and external integration.Taking into account these principles, an updated interpretation of the main levels of higher education (Bachelor’s, Specialist’s, Master’s, Postgraduate) is proposed, a new vision of a multi-format Master’s program is presented. The author formulates proposals regarding flexibility of study periods at all levels and possible schemes for building individual educational trajectories in the system of inter-level mobility. Transition from the paradigm of the level system of higher education to the paradigm of the integrated education system is substantiated as a promising growth vector.